Access and identity management for libraries controlling access to online information - Garibyan, Masha ca. 20./21. Jh; McLeish, Simon ca. 20./21. Jh; Paschoud, John ca. 20./21. Jh (Facet Publishing, 2014)
This book provides practical guidance to ensuring that your users can access and personalise the online resources they are entitled to use with the minimum of fuss. With the rapid increase in the use of electronic resources in libraries, managing access to online information is an area many librarians struggle with. Managers of online information wish to implement policies about who can access the information and under what terms and conditions but often they need further guidance. Written by experts in the field, this practical book is the first to explain the principles behind access management, the available technologies and how they work. This includes an overview of federated access management technologies, such as Shibboleth, that have gained increasing international recognition in recent years. This book provides detailed case studies describing how access management is being implemented at organizational and national levels in the UK, USA and Europe, and gives a practical guide to the resources available to help plan, implement and operate access management in libraries. Key topics include: what is access management and why do libraries do it?; electronic resources: public and not so public; principles and definitions of identity and access management; current access management technologies; authentication technologies; authorization based on physical location; authorization based on user identity or affiliation; federated access: history, current position and future developments; internet access provided by (or in) libraries; library statistics; the business case for libraries. This is essential reading for all who need to understand the principles behind access management or implement a working system in their library